Severe mitral regurgitation due to geometric changes in the mitral valve after surgical aortic valve replacement - Wakabayashi, Ryo (JA Clin Rep, 2019)
BACKGROUND: Severe mitral regurgitation (MR) after aortic valve replacement (AVR) is a serious complication. Although several causes of MR after AVR have been reported, severe MR due to geometric changes in the mitral valve imposed by an aortic valve prosthesis has not been reported. We here report a case of severe MR after AVR that was improved after re-AVR. CASE PRESENTATION: A 77-year-old male underwent elective total aortic arch replacement and AVR. Mild MR was preoperatively identified. After surgery and separation from cardiopulmonary bypass, transesophageal echocardiography (TEE) demonstrated restriction and distortion of the anterior mitral leaflet and severe MR. Displacement of the anterior mitral annulus by the prosthetic aortic valve was strongly suspected to be the cause of MR, which should be surgically restored. Re-AVR using a small-sized valve was then performed. Consequently, the structural changes in the mitral valve were reverted and the MR was reduced. CONCLUSIONS: Geometric changes in the mitral valve induced by an aortic valve prosthesis can cause massive increment of MR. Intraoperative TEE examination of the mitral apparatus is important when severe MR occurs after AVR.